2003
DOI: 10.1007/978-3-540-39762-5_35
|View full text |Cite
|
Sign up to set email alerts
|

Power Estimation Approach of Dynamic Data Storage on a Hardware Software Boundary Level

Abstract: Abstract. In current multimedia applications like 3D graphical processing or games, the run-time memory management support has to allow real-time memory de/allocation, retrieving and data processing. The implementations of these algorithms for embedded platforms require high speed, low power and large data storage capacity. Due to the large hardware/software co-design space, high-level implementation cost estimates are required to avoid expensive design modifications late in the implementation. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2
2
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…After implementing and profiling these two generic DM managers, we have observed that most of the accesses in Kingsley occur in just few of the "bins" (or memory pools of the heap) [15], due to the limited range of data type sizes used in the application [5]. Therefore, we try to reduce its memory waste by modifying its design with our layers and by limiting the number of bins to the actual sizes used in the application (5 main sizes), as Figure 4 shows at the top in its right graph.…”
Section: Case Studies and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After implementing and profiling these two generic DM managers, we have observed that most of the accesses in Kingsley occur in just few of the "bins" (or memory pools of the heap) [15], due to the limited range of data type sizes used in the application [5]. Therefore, we try to reduce its memory waste by modifying its design with our layers and by limiting the number of bins to the actual sizes used in the application (5 main sizes), as Figure 4 shows at the top in its right graph.…”
Section: Case Studies and Experimental Resultsmentioning
confidence: 99%
“…Since more than one layer can constitute the part of the manager to measure, the profiling information must be grouped and cannot be collected at one layer only. Therefore, we have integrated a similar approach to the one proposed in [5] for complex dynamic data types. As Figure 3 depicts, it consists of an object-oriented profiling framework that decouples this information from the class hierarchy of the DM managers, providing accurate run time information on memory accesses, memory footprint, timing information and method calls.…”
Section: Structured Profile Framework and Power Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The first phase of our approach (number 1 in Figure 2) is an analysis of the run-time de/allocation and access behavior (i.e., reads and writes) of each DDT in the application under study. This is possible thanks to the use of our previous work, namely profiling tools for DDTs [10] and the exploration of custom DM managers [1]. The analysis of the first phase of our approach reveals the spatial (also temporal) locality of the DDTs in the dynamic application, which are mainly linked to the logical phases of the algorithms involved in the application (see Section 6 for real examples).…”
Section: Efficient Use Of the Memory Hierarchy For Dm Managementmentioning
confidence: 99%
“…First, we compute the read and write accesses to the cache, scratchpad and main memory with the profiling data of: (i) the DDTs and (ii) the dynamic memory management mechanism as we explained in our previous work, i.e., [10] and [1] respectively. Next, to evaluate the cache hits and misses we use the very well known Dinero IV cache simulator [11].…”
Section: Energy Consumption Modeling In Memory Architecturesmentioning
confidence: 99%